PENILAIAN PRIORITAS PENGEMBANGAN PELABUHAN LAUT DI INDONESIA - Edyanto, CB Herman (Badan Pengkajian dan Penerapan Teknologi, 2010)
As an archipelagic country, Indonesia relies heavily on good sea transportation system to support national economic development, to achieve a sustainable logistical distribution system over the country and to help maintain the national unity. To achieve this goal, a good port system should be in place. Port is one of the most important urban facilities where people could continue their travel from one to another place. It is build for several purposes such as : trading, basic for military expansion , fishing, and travelling . But it was not much realized by the people that the establishment of port has an effect to the existence of regional economic development . There are 68 ports in Indonesia which are situated in five big islands namely Java, Sumatra, Kalimantan, Sulawesi, West Papua and two small islands namely : East Nusatenggara, and also West Nusatenggara. Four ports are identified as potential ports to be developed at national scale based on infrastructure sensitivity level for regional development